Information-seeking behavior of the Ulama in relation to preaching and counseling roles in Nigeria - Saleh, Adam Gambo; Abu Bakar, Ahmad Bakeri (American Theological Library Association, 2013)
The study of information-seeking behavior has over the years attracted the attention of information professionals, resulting in numerous studies conducted with a view to understanding why people seek information, how they seek it, and the problems they encounter. While the information-seeking behavior of several professional groups has been studied, an important and influential group of professionals, Muslim clerics (Ulama; sing.--Alim) has been totally neglected. Thus, the main objective of this study was to investigate the information-seeking behavior of the Ulama in a developing country. The study investigated such questions as how do the Ulama in Nigeria seek information to perform their preaching and counseling roles? What search strategies do they deploy? Is there a relationship between demographic factors and information seeking patterns? The study used the survey research method. The target population was made up of 973 Ulama dispersed within 27 Local Government Areas of Borno State in Nigeria. A proportional stratified random sampling technique was used to arrive at the sample size of 281. The study used a questionnaire to collect data which was subjected to both descriptive and inferential statistical analyses. The study found out that the Ulama consult different sources and resources for different roles. For purposes of preaching, the Ulama mostly consult their personal collections to use resources such as the Qur’an, Hadith, and commentaries by other scholars. However, when performing a counseling role, they consult secular resources and informal channels of information such as council of Ulama, colleagues, or friends and relatives. The study also found out that the Ulama deployed different search strategies to identify and locate information when using public and institutional libraries, information and communication technology facilities, or informal channels. The study has also established significant relationships between demographic factors and search strategies adopted. Finally, the study identified the similarities and differences between the information-seeking behaviors of the Christian clergy and the Ulama.